2014
DOI: 10.1007/s10120-014-0416-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial dysplasia of the stomach with gastric immunophenotype shows features of biological aggressiveness

Abstract: Background Gastric dysplasia is classified as adenomatous/type I (intestinal phenotype) and foveolar or pyloric/ type II (gastric phenotype) according to morphological (architectural and cytological) features. The immunophenotypic classification of dysplasia, based on the expression of the mucins, CD10 and CDX2, recognizes the following immunophenotypes: intestinal (MUC2, CD10, and CDX2); gastric (MUC5AC and/or MUC6, absence of CD10, and absent or low expression of CDX2); hybrid (gastric and intestinal markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Several authors have found differential genetic and epigenetic alterations in gastric versus intestinal phenotypes [50,51], although the association with specific clinicopathological features and the prognosis is still conflicting [45,51]. During GC progression, a phenotypic switch may occur from gastric to intestinal differentiation [45]; moreover, some authors hypothesise that GC with a gastric phenotype may also progress to poorly differentiated GC [44,47].…”
Section: Morphological Heterogeneity Of Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have found differential genetic and epigenetic alterations in gastric versus intestinal phenotypes [50,51], although the association with specific clinicopathological features and the prognosis is still conflicting [45,51]. During GC progression, a phenotypic switch may occur from gastric to intestinal differentiation [45]; moreover, some authors hypothesise that GC with a gastric phenotype may also progress to poorly differentiated GC [44,47].…”
Section: Morphological Heterogeneity Of Gcmentioning
confidence: 99%
“…According to their expression, four GC immunophenotypes have been recognised: the intestinal (expressing MUC2, CD10, CDX2), gastric (expressing MUC5AC/TTF1 and/ or MUC6/TTF2), hybrid (expressing intestinal and gastric markers), and null phenotype [43][44][45][46]. These phenotypes have also been recognised in GC precursor lesions [47][48][49]. Several authors have found differential genetic and epigenetic alterations in gastric versus intestinal phenotypes [50,51], although the association with specific clinicopathological features and the prognosis is still conflicting [45,51].…”
Section: Morphological Heterogeneity Of Gcmentioning
confidence: 99%
“…Despite a considerable decrease in the incidence of gastric cancer (GC) in many developed countries, GC remains the fourth most commonly diagnosed malignancy and the second leading cause of cancer-related death worldwide [1,2]. In the past few decades, standard multimodal treatment strategies have been used to improve outcomes in patients with GC, particularly those with advanced and metastatic diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this variant originates in the native or non-metaplastic gastric mucosa, rather than in intestinal metaplastic lesions with the involvement of spasmolytic polypeptide-expressing metaplasia (SPEM) pathway of carcinogenesis. 40 There are no validated criteria for morphologically establishing a hybrid phenotype (with both adenomatous and gastric differentiation). In such instances, the immunohistochemical expression of MUC proteins (MUC2, MUC5AC and MUC6), CDX2, and CD10 have been used to establish the mixed lineage.…”
Section: Phenotype Based Risk Of Carcinomamentioning
confidence: 99%